Microbiome and plant cell transformation trigger insect gall induction in cassava - Gätjens-Boniche, Omar; Jiménez-Madrigal, Jose Pablo; Whetten, Ross W.; Valenzuela-Diaz, Sandro; Alemán-Gutiérrez, Alvaro; Hanson, Paul E.; Pinto-Tomás, Adrián A. (Frontiers in Plant Science, 2023)
Several specialised insects can manipulate normal plant development to induce a highly organised structure known as a gall, which represents one of the most complex interactions between insects and plants. Thus far, the mechanism for insect-induced plant galls has remained elusive. To study the induction mechanism of insect galls, we selected the gall induced by Iatrophobia brasiliensis (Diptera: Cecidomyiidae) in cassava (Euphorbiaceae: Manihot esculenta Crantz) as our model. PCR-based molecular markers and deep metagenomic sequencing data were employed to analyse the gall microbiome and to test the hypothesis that gall cells are genetically transformed by insect vectored bacteria. A shotgun sequencing discrimination approach was implemented to selectively discriminate between foreign DNA and the reference host plant genome. Several known candidate insertion sequences were identified, the most significant being DNA sequences found in bacterial genes related to the transcription regulatory factor CadR, cadmium-transporting ATPase encoded by the cadA gene, nitrate transport permease protein (nrtB gene), and arsenical pump ATPase (arsA gene). In addition, a DNA fragment associated with ubiquitin-like gene E2 was identified as a potential accessory genetic element involved in gall induction mechanism. Furthermore, our results suggest that the increased quality and rapid development of gall tissue are mostly driven by microbiome enrichment and the acquisition of critical endophytes. An initial gall-like structure was experimentally obtained in M. esculenta cultured tissues through inoculation assays using a Rhodococcus bacterial strain that originated from the inducing insect, which we related to the gall induction process. We provide evidence that the modification of the endophytic microbiome and the genetic transformation of plant cells in M. esculenta are two essential requirements for insect-induced gall formation. Based on these findings and having observed the same potential DNA marker in galls from other plant species (ubiquitin-like gene E2), we speculate that bacterially mediated genetic transformation of plant cells may represent a more widespread gall induction mechanism found in nature.